PENERAPAN PEMBELAJARAN MAHARAH KALAM BERBASIS TEORI KONSTRUKTIVISME DI MADRASAH ALIYAH NASY’ATUL MUTA’ALLIMIN - Al-Ghozali, M. Dzikrul Hakim; Rofiq, Aji Ainur (JoEMS (Journal of Education and Management Studies), 2021)
Maharah Kalam learning is a problem of traditional Arabic learning methods (based on behaviorism theory, where students are passive which has implications for learning outcomes and students' abilities in understanding the studies being studied for Arabic proficiency. In constructivism, learning is represented as a constructive process in which students internal illustration of knowledge, interpretation of personal experience Constructivism learning based on student interaction in construction and knowledge How about the Maharah Kalam learning method based on constructivism theory at MA Nasy'atul Muta'allimin, and problematic Maharah Kalam learning at MA Nasy' atul Muta'allimin Method The method used is through observation, interviews, and documentation. Techniques and data analysis using descriptive analysis. The results of the study show that at MA Nasy'atul Muta'allimin, which previously had not applied constructivism learning theory, g has implications for the low ability of students' Maharah Kalam. Then with the presence of constructivism learning methods become effective and able to build students' knowledge and improve language skills actively and creatively.